2022
DOI: 10.3390/agronomy12071613
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen and Phosphorus Addition on Agronomic Characters, Photosynthetic Performance and Anatomical Structure of Alfalfa in Northern Xinjiang, China

Abstract: The productivity of alfalfa is associated with a large amount of nitrogen (N) and phosphorus (P); the addition of exogenous N and P fertilizers can fully exploit the growth potential of alfalfa. However, there is uncertainty about the relationship between changes in alfalfa productivity and photosynthetic physiology and anatomy. We conducted field fertilization experiments on alfalfa in the second and third years under drip irrigation, as well as measurement of the photosynthetic physiology, anatomical structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…These results are consistent with those of Sugiura et al 11 . High MVB XW and MVB PW values indicate high sugar and water transport capacity of phloem, which is not only beneficial to unload excess nonstructural carbohydrates in leaves, 11 but also provides sufficient water for crop leaves under deficit irrigation 41 . The VIP analysis also confirmed this finding.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with those of Sugiura et al 11 . High MVB XW and MVB PW values indicate high sugar and water transport capacity of phloem, which is not only beneficial to unload excess nonstructural carbohydrates in leaves, 11 but also provides sufficient water for crop leaves under deficit irrigation 41 . The VIP analysis also confirmed this finding.…”
Section: Discussionsupporting
confidence: 91%
“…3; Supplementary Table 1). Excessive P enhances plant respiration, which demands large amounts of sugar and energy; this thickens and darkens leaves while reducing the rate of photosynthesis (Malhotra et al 2018;Sun et al 2022). In addition, excessive P content can induce nutrient deficiencies in Fe, Zn, and Mg, as the combination of phosphate and metal ions forms insoluble substances in the soil (Osman and Osman 2013;Sharma et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that lowlatitude areas can lead to lower over-summering rates of alfalfa due to high temperatures and continuous rainfall. Additionally, soil nutrients and beneficial microorganisms may vary increasingly with the growing year due to the inconsistent growth characteristics and nutrient requirements of different alfalfa varieties [31]. In conclusion, the growth differences of different fall-dormancy alfalfa are mainly influenced by various factors such as latitude, climatic environment, and their own genetics.…”
Section: Effect Of Fall-dormancy Level On Persistence and Yield Of Al...mentioning
confidence: 97%